2022
DOI: 10.3390/foods11233928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sous Vide Cooking on the Physicochemical and Volatile Flavor Properties of Half-Shell Scallop (Chlamys farreri) during Chilled Storage

Abstract: This study explored the effects of sous vide (SV) cooking treatments on the physicochemical quality and volatile flavor of half-shell scallop (Chlamys farreri) during 30 d of chilled storage. The vacuum-packed scallop samples were cooked at 70 °C (SV-70) and 75 °C (SV-75) and maintained for 30 min. The samples were compared with the positive control (cooked at 100 °C for 10 min, CK). The results indicate that the total volatile basic nitrogen (TVBN), pH, texture, and malondialdehyde (MDA) content gradually inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…At the end of storage, TVB-N values of all groups were determined below the acceptable limit (≤35 mg/100 g) (Varlık et al, 1993). Similarly, Zhan et al (2022) found that the TVB-N contents of three groups of scallop samples cooked at different temperatures (70ºC and 75ºC) with control and sous vide techniques increased with increasing storage time. Kurt Kaya (2022) emphasized that when the quality of marinated crayfish was examined in brine, vacuum packaging and sous-vide cooking, increases were detected depending on time in all groups during storage (p < 0.05).…”
Section: Ph Tbars and Tvb-nmentioning
confidence: 74%
“…At the end of storage, TVB-N values of all groups were determined below the acceptable limit (≤35 mg/100 g) (Varlık et al, 1993). Similarly, Zhan et al (2022) found that the TVB-N contents of three groups of scallop samples cooked at different temperatures (70ºC and 75ºC) with control and sous vide techniques increased with increasing storage time. Kurt Kaya (2022) emphasized that when the quality of marinated crayfish was examined in brine, vacuum packaging and sous-vide cooking, increases were detected depending on time in all groups during storage (p < 0.05).…”
Section: Ph Tbars and Tvb-nmentioning
confidence: 74%
“…Consumer demand for marine shellfish has significantly increased in recent decades [2,3]. Due to the lack of information about the nutritional value of the most edible bivalves, it is important to provide consumers with useful and applicable information about their beneficial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for seafood has been rapidly rising, driven by increases in populations and their rising purchasing power. According to the literature, the leading drivers of seafood consumption are nutrition, taste and convenience [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to a previously reported method ( Zhan et al, 2022 ), the minced whitespotted conger meat (3.0 g) was added to buffer A (15.0 mL) containing Tris-HCl (10.0 mmol/L, pH 7.2) and homogenized (T18, IKA, Guangzhou, China) for 3 min with 30 s interval. After the mixture was centrifuged at 6000 rpm for 10min (4 °C), the supernatant was extracted again.…”
Section: Methodsmentioning
confidence: 99%